PEMBERDAYAAN TANAH WAKAF YANG DIKELOLA YAYASAN BERDASARKAN NILAI KEADILAN - Sutrisno Sutrisno (UNISSULA, 2017)
Wakaf was originally done by oral means intended for worship activities such as mosques,mosques, madrassas or tombs. The existence of such representation has been running since theentry of Islam in the Nusantara. After Indonesia’s independence, the rules on the procedure ofregulation began to be arranged as proven by the issuance of Government Regulation Number28 Year 1977 regarding Ownership of Land Ownership. The provisions in this regulation governthe representation of the land as well as procedures and procedures written endowments pouredin the Deed of Pledge Wakaf. Then followed by the issuance of Presidential Instruction No. 1of 1991 on the Compilation of Islamic Law which regulates the wakaf of moving goods or notmoving. The research approach used in this research is sociological legal method or socio-legalresearch approach. The result of research indicates that one of the causes of empowerment ofwaqf land managed by foundations is not based on the value of justice due to the low level ofhuman resources and professionalism of individual Nadzir in the management of wakaf land atthis time get less attention and also special coaching from BWI and Kemenag. So that the numberof unproductive, abandoned and even lost wakaf land and one weakness of empowerment ofwakaf land managed by the foundation now is Nadzir, Waqf Board of Indonesia and Ministry ofReligious Affairs have little active role in carrying out their respective duties as specified in theLaws and Regulations, Invite waqf.